Multiple Modes of Nematode Control by Volatiles of Pseudomonas putida 1A00316 from Antarctic Soil against Meloidogyne incognita - Zhai, Yile; Shao, Zongze; Cai, Minmin; Zheng, Longyu; Li, Guangyu; Huang, Dian; Cheng, Wanli; Thomashow, Linda S.; Weller, David M.; Yu, Ziniu; Zhang, Jibin (Frontiers in Microbiology, 2018)
Pseudomonas putida 1A00316 isolated from Antarctic soil showed nematicidal potential for biological control of Meloidogyne incognita; however, little was known about whether strain 1A00316 could produce volatile organic compounds (VOCs), and if they had potential for use in biological control against M. incognita. In this study, VOCs produced by a culture filtrate of P. putida 1A00316 were evaluated by in vitro experiments in three-compartment Petri dishes and 96-well culture plates. Our results showed that M. incognita juveniles gradually reduced their movement within 24–48 h of incubation with mortality ranging from 6.49 to 86.19%, and mostly stopped action after 72 h. Moreover, egg hatching in culture filtrates of strain 1A00316 was much reduced compared to that in sterile distilled water or culture medium. Volatiles from P. putida 1A00316 analysis carried out by solid-phase micro-extraction gas chromatography–mass spectrometry (SPME-GC/MS) included dimethyl-disulfide, 1-undecene, 2-nonanone, 2-octanone, (Z)-hexen-1-ol acetate, 2-undecanone, and 1-(ethenyloxy)-octadecane. Of these, dimethyl-disulfide, 2-nonanone, 2-octanone, (Z)-hexen-1-ol acetate, and 2-undecanone had strong nematicidal activity against M. incognita J2 larvae by direct-contact in 96-well culture plates, and only 2-undecanone acted as a fumigant. In addition, the seven VOCs inhibited egg hatching of M. incognita both by direct-contact and by fumigation. All of the seven VOCs repelled M. incognita J2 juveniles in 2% water agar Petri plates. These results show that VOCs from strain 1A00316 act on different stages in the development of M. incognita via nematicidal, fumigant, and repellent activities and have potential for development as agents with multiple modes of control of root-knot nematodes.